Batik and Tenun Endek Diplomacy as a Cultural Legacy from Soeharto’s to Jokowi’s Administration - Steelyana, Evi; WawoRuntu, Ine (Bina Nusantara University, 2024)
The research explored an interesting relationship between Indonesian cultural heritage and international relations. It focused on Batik Indonesia and Tenun Endek Bali as strategic tools for cultural diplomacy efforts across different presidential administrations. Starting with President Soeharto’s use of Batik as a gift at the United Nations in the 1980s, these textiles have appeared at six major ASEAN and APEC Summits. The key research question was whether these gorgeous textiles had been effective in promoting Indonesian culture on a global stage. The research aimed to analyze the evolution of Batik Indonesia and Tenun Endek Bali, emphasizing significant international events where they gained recognition, such as the ASEAN and APEC Summits. The research applied a qualitative method and archival content to analyze the journey of batik and Tenun Endek Bali in Indonesian diplomacy. The findings present a compelling narrative. The research suggests a potential link between the use of batik and Tenun Endek and positive outcomes at global meetings, including free trade (APEC 1994), regional cooperation (ASEAN Summit 2011), and consensus building (G20 2023). This highlights Indonesia’s evolving role on the international stage. The research offers a fresh perspective by examining the long-term use of batik and Tenun Endek Bali by Indonesian presidents as cultural diplomacy tools at global events, proposing a novel link to positive outcomes, and highlighting cultural heritage’s potential as a ‘soft power’ diplomatic strategy.